2019
DOI: 10.15420/ecr.2019.30.2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Recurrence of AF in Patients After Radiofrequency Ablation

Abstract: Catheter ablation is a well-known treatment for patients with AF. Despite the growing knowledge in the field, the identification of predictors of recurrence of AF after catheter ablation is one of the primary goals and is of major importance to improve long-term results of the procedure. The aim of this article is to provide an overview of what has been published in recent years and to summarise the major predictors, helping cardiac electrophysiologists in the selection of the right candidates for catheter abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 53 publications
2
28
0
1
Order By: Relevance
“…The most challenging issue in managing patients with AF is identifying those predictors for unsuccessful ablation. A large number of studies determined the risk factors for poor outcome following PVI as nonparoxysmal AF (particularly longstanding persistent AF), LA dilatation and higher CHA 2 DS 2 -VASc score, which was con rmed in our trial [2,8,9,12]. In our study, MV ordinal logistic regression analysis found an independent association between PVIOD and LA diameter, CHA 2 DS 2 -VASc score and AF type.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The most challenging issue in managing patients with AF is identifying those predictors for unsuccessful ablation. A large number of studies determined the risk factors for poor outcome following PVI as nonparoxysmal AF (particularly longstanding persistent AF), LA dilatation and higher CHA 2 DS 2 -VASc score, which was con rmed in our trial [2,8,9,12]. In our study, MV ordinal logistic regression analysis found an independent association between PVIOD and LA diameter, CHA 2 DS 2 -VASc score and AF type.…”
Section: Discussionsupporting
confidence: 79%
“…In the modern era, after multiple catheter ablations and additional substrate modi cation (ASM), long-term success was 62-79.5% in paroxysmal AF, 46.2-68.2% in persistent AF and 39-41% in longstanding persistent AF [3][4][5][6][7]. Many studies have explored the predictors of arrhythmia recurrence, such as non-paroxysmal AF, female sex, longer AF duration prior to the catheter ablation, sleep apnea, obesity, elderly patients, hypertension, structural heart disease, enlarged left atrial (LA) diameter, higher CHADS 2 , CHA 2 DS 2 -VASc, MB-LATER and APPLE scores, low LA voltage, C-reactive protein and increased LA brosis detected by cardiac magnetic resonance imaging [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Many recent references showed that P-wave duration decreases once catheter ablation ends [ 11 , 14 , 15 , 17 , 18 , 37 ], and heart rate increases (RR interval decreases) [ 38 , 39 , 40 ]. Our results are in line with these previous references.…”
Section: Discussionmentioning
confidence: 99%
“…Shortened P-wave duration is associated with a successful PVI outcome and lower rates of AF recurrence. However, despite the growing knowledge in the field, the identification of changes induced in the atrial substrate that yield a successful PVI are of paramount importance for the clinical management of the arrhythmia [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…AF ablation is associated with various recurrence rates, mostly due to patient-specific preprocedural factors and specific procedural factors [ 14 ]. Predictors of recurrence after AF ablation divided depending on underling structural, electrical, and autonomic substrate [ 14 , 15 ]. In this study, age, non-paroxysmal AF, overweight/obesity, hypertension, diabetes mellitus, LA diameter, MR LGE, and AF duration were found to be associated with AF recurrence by univariate analysis.…”
Section: Discussionmentioning
confidence: 99%